State-of-charge dynamic balancing strategy for distributed energy storage system in DC shipboard microgrid. (December 2021) - Zeng, Yuji; Zhang, Qinjin; Liu, Yancheng; Zhuang, Xuzhou; Che, Long; Niu, Miao; Zheng, Xianglu
Highlights: A novel SoC dynamic balancing control strategy for DESUs in DC shipboard microgrid is proposed. A secondary compensation method is proposed to restore DC-bus voltage. The SoC equalization speed and accuracy are improved without causing bus voltage drop. The SoC balance can be achieve in both communication normal and failure conditions. The SoC balance and current sharing performance of the DESUs with the same and different capacitys are verified. Abstract: In this paper, a State-of-Charge (SoC) dynamic balancing control strategy considering system communication failure and energy storage capacity difference is proposed to reach the SoC balancing and proper current sharing for distributed energy storage units (DESUs) in DC shipboard microgrid. Firstly, the distributed equalization algorithm is applied in the DESU's controller when the system communication is normal, each DESU exchanges their SoC information through low bandwidth communication (LBC) and dynamically adjusts the droop coefficient according to the change of their SoC, so as to realize the SoC dynamic balance of the energy storage system. Secondly, the DESU's controller is switched to the decentralized equalization algorithm with communication failure, each DESU can reach SoC balancing and load current reasonable distribution only according to the local information. After that, a DC bus voltage compensation method is introduced to solve the problem of bus voltage deviation caused by the proposed SoC equalization. Finally, the simulation model comprised of three DESUs is implemented and the results show that the proposed control strategy can make each DESU reach SoC equilibrium state quickly and effectively reduce the bus voltage deviation under the normal and failure communication conditions.